Mandibular Brown Tumor of Secondary Hyperparathyroidism Requiring Extensive Resection: A Forgotten Entity in the Developed World? - Mohammed Qaisi; Matthew Loeb; Lindsay Montague; Ron Caloss (Case Reports in Medicine)
Brown tumor of hyperparathyroidism (BTHPT) is rare in the United States and not frequently seen in clinical practice. This is likely because early diagnosis and prompt treatment of this disease process prevent the progression and development of BTHPT. Conversely, BTHPT is more common in underdeveloped countries where fewer patients have access to health care and hyperparathyroidism (HPT) goes untreated. It has been reported that the incidence of BTHPT in underdeveloped countries can be as high as 58 to 69 percent in patients with primary HPT. We present a case report of a patient in the United States with a large mandibular BTHPT requiring an extensive resection in the setting of secondary HPT. Despite being rare in this country, it is important for nephrologists, primary care physicians, and oral health care providers to be able to recognize this entity, so that intervention may be rendered early.